Peer Review Process in Turkey for Journals Regarding Social and Human Sciences: A Study from the Perspectives of Author, Peer Reviewer and Editor - Hülya Dilek-Kayaoğlu; Mehmet Tayfun Gülle (Türk Kütüphaneciliği)
The main purpose of this study is to examine the peer review process in Turkey, from the perspectives of authors, peer reviewers and editors of social and human sciences. Thus, the attitudes and behaviors of the parties participated in that process and of which roles are usually overlapped (author, peer reviewer and editor) and the problems they experienced can be determined at first hand and valuable data that can contribute to enhance in qualification and activation of the process and/or in questioning of the process. A web based survey is conducted to achieve this purpose. The survey results reveal that the authors, the peer reviewers and the editors support the peer review system in social and human sciences, in principle. A very large majority of the respondents agreed or strongly agreed with the statement, “There is no control in scientific communication without formal peer review.” On the contrary only three percent of the total respondents agreed or strongly agreed with the statement, “Peer review system is useless.” Furthermore, approximately one-fourth of the respondents agreed or strongly agreed with the statement, “Current peer review system is the best we could do.” These findings suggest that the majority regard peer review as a mechanism providing control on quality but the current peer review system is not the best we could do and improvements can be made to make it better. Based on these and other survey findings, the authors of the article make suggestions for improvement.